Design a Web-Based Library Information System Using the Waterfall Method (Case Study of SMA Muhammadiyah 2) - Nur Aulia, Adiva; Tsani, Mutiara; Suharso, Wildan (Universitas Ibn Khaldun Bogor, 2024)
Information technology is a technology that is developing rapidly at this time. Computers as student learning media have many functions such as audio, animation, visual, and interactive capabilities. The main problem in the field of education is the low interest in reading students and reading habits. The library is expected to help increase students' interest in reading and reading habits. SMA Muhammadiyah has a new library and is still manual in recording borrowing and returning books. This makes it difficult for librarians to search for data and is at risk of losing books. It is difficult for students to find book information and the irregular placement of books makes the process of borrowing books ineffective and inefficient. Therefore, a web-based library information system is needed to make it easier for students to borrow books. The Waterfall method will be used to help design the library system at SMA Muhammadiyah 2 Cipondoh. The Waterfall method is a method that is very commonly used in the early stages of the manufacturing process. Application features developed by researchers at the Muhammadiyah 2 Cipondoh High School library include logins, book master data, book loan transaction data, book return transaction data, and book borrowing reports. Library information system development uses the PHP CodeIgniter 3 framework. The front ends used are HTML 5, CSS 3, and Bootstrap version 4.